2006
DOI: 10.3819/ccbr.2008.20001
|View full text |Cite
|
Sign up to set email alerts
|

Tool-Related Cognition in New Caledonian Crows

Abstract: The extent to which non-humans understand their physical world is controversial, due to conceptual and empirical difficulties. We examine the evidence for physical understanding in the remarkable tool-oriented behaviour of New Caledonian crows, which make several types of tool in the wild and show prolific tool-related behaviour in captivity. We summarize our own research into the cognitive processes involved in tool behaviour in this species, and review comparable studies in other birds and primates. Our main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 108 publications
0
62
0
3
Order By: Relevance
“…The present study addressed the need, noted by Bluff et al (2007), for a comparison between corvids' tool selections and those of humans and other primates. This study showed that, unlike some New Caledonian crows tested with similar tasks (see, e.g., Chappell & Kacelnik, 2002), people did not generally select a stick tool whose length matched the distance over which a desired object had to be retrieved.…”
Section: Genera R R L Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study addressed the need, noted by Bluff et al (2007), for a comparison between corvids' tool selections and those of humans and other primates. This study showed that, unlike some New Caledonian crows tested with similar tasks (see, e.g., Chappell & Kacelnik, 2002), people did not generally select a stick tool whose length matched the distance over which a desired object had to be retrieved.…”
Section: Genera R R L Discussionmentioning
confidence: 99%
“…The position of any individual stick varied randomly between participants. intelligent animals, notably humans and other primates" (Bluff, Weir, Rutz, Wimpenny, & Kacelnik, 2007, p. 20), it is difficult to answer the question of whether corvids' tool use is more aptly described as a species-specific adaptation to procuring food or as evidence of their physical intelligence (Bluff et al, 2007;Emery, 2004;). Using adult humans as subjects allows us to examine tool use and selectivity while assuming with some degree of certainty that a participant's behavior is not caused by the activation of species-typical reward-related sensitivities and actions (e.g., for some animals, solving a "detour problem," in which it is necessary to push a food reward farther away before it can be obtained, may be difficult if these animals are predisposed to engage in actions that bring food nearer), cognitive deficits (e.g., inability to understand causal constructs such as gravity, transfer of force, and connectivity), or imposing too great a cognitive load (e.g., requiring the participant to attend to, and remember, too many aspects of the problem and steps in potential solutions).…”
Section: Methodsmentioning
confidence: 99%
“…However, the idea goes deeper than that. A house sparrow will probably not be able to make tools like a New Caledonian crow [48] even if it pays careful attention to twigs and leaves, and tries to accumulate data about them. This is almost like expecting that a dog will be able to understand English if it only listens carefully to its owners and acquires long enough strings of spoken language.…”
Section: Evolving Brainsmentioning
confidence: 99%
“…However, the ape's technology goes far beyond subsistence, notably into social and self-maintenance realms, neither of which is expressed by the crow, as seen in the ranges of functions displayed. Finally, despite the impressive range of social cognition displayed by other corvid species [17 -19], it is unclear whether NCC's cognition extends into higher-order cognition, such as theory of mind [16,70,89]. Thus, the chimpanzee is a truly generalist technologist, more akin to the other hominins than to any other living non-hominin species [37].…”
Section: Resultsmentioning
confidence: 99%
“…An extended version of this task involves an extra step, whereby three tools are necessary to solve the problem [88]. A variant design has the crows obtaining the first tool by pulling up a string, then using it to extract a long-enough tool from a toolbox, then using the long tool to extract food from a cavity [89].…”
Section: Modes Of Associative Technologymentioning
confidence: 99%